Oteseconazole versus fluconazole for the treatment of severe vulvovaginal candidiasis: a multicenter, randomized, double-blinded, phase 3 trial - Wang, Xiaoqian; Chen, Lihong; Ruan, Hongjie; Xiong, Zhengai; Wang, Wenying; Qiu, Jin; Song, Weihua; Zhang, Chunlian; Xue, Fengxia; Qin, Tianhua; Zhang, Bei; An, Ruifang; et al. (Antimicrobial agents and chemotherapy, 2024)
Vulvovaginal candidiasis (VVC) is a common condition among women. Fluconazole remains the dominant treatment option for VVC. Oteseconazole is a highly selective inhibitor of fungal CYP51. This randomized, double-blinded, phase 3 trial was conducted to evaluate the efficacy and safety of oteseconazole compared with fluconazole in treating severe VVC. Female subjects presenting with vulvovaginal signs and symptoms score of ≥7 and positive infection determined by potassium hydroxide test or Gram staining were randomly assigned to receive oteseconazole (600 mg on D1 and 450 mg on D2) or fluconazole (150 mg on D1 and D4) in a 1:1 ratio. The primary endpoint was the proportion of subjects achieving therapeutic cure [defined as achieving both clinical cure (absence of signs and symptoms of VVC) and mycological cure (negative culture of species)] at D28. A total of 322 subjects were randomized and 321 subjects were treated. At D28, a statistically significantly higher proportion of subjects achieved therapeutic cure in the oteseconazole group than in the fluconazole group (66.88% vs 45.91%; = 0.0002). Oteseconazole treatment resulted in an increased proportion of subjects achieving mycological cure (82.50% vs 59.12%; < 0.0001) and clinical cure (71.25% vs 55.97%; = 0.0046) compared with fluconazole. The incidence of treatment-emergent adverse events was similar between the two groups. No subjects discontinued study treatment or withdrew study due to adverse events. Oteseconazole showed statistically significant and clinically meaningful superiority over fluconazole for the treatment of severe VVC and was generally tolerated.